The Trends of English Language Teaching After Pandemic Covid-19: A Review of Second Language Acquisition Methods for Online Approach - Mohammad Huzaifa Siddiqui; Zeeshan Memon; Nouman Zafar Jatoi; Tahreem Akhter Surahio (Social Science Review Archives, 2025)
The study pursues the shift of trends in English language teaching (ELT) as a second language after COVID-19 in Pakistan. COVID-19 has changed the world in various means, similarly, the teaching methods are also changed. This study encounters the problems ELT teachers and students face following the procedures of Second Language Teaching i.e., English language teaching during online classrooms. For example, teachers need professional training to tackle many students creatively. It becomes challenging for them to follow second language approaches to teach specific skills to students. Teachers can create a natural and motivational environment for the learners in online classrooms if the online classrooms are fully equipped with resources. The aim is to highlight where developed countries enjoy the advantages of online teaching and learning, Pakistan faces disadvantages and several challenges due to poor infrastructure of technology in education and internet unavailability. The study uses a quantitative approach. The questionnaires were distributed among 30 English language teachers affiliated with well-known government/ private institutes of Pakistan, Sindh region. They were given close-ended questions related to their teaching styles and methods in online classrooms for four skills. The responses were analyzed. The results outcomes some key facts as a priority and challenges for the development of a Second language teaching and learning via online approach. The results also emphasize that English language teachers have trouble teaching grammar rules via an online approach. The finding concluded that the online teaching approach requires a bundle of resources i.e., quizzes, PowerPoint presentations, online games, and samples of the writing and reading tasks for sustaining students’ motivation for second language learning.